(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Various different researchers have studied the relationship among the FDI in agriculture, poverty, inflation, technology, and infrastructure separately. The gap in this study is that research regarding the impact of poverty on the growth of the agricultural sector due to foreign direct investment (FDI) is rarely done. Most of the research is done regarding the developing countries. The countries selected to study, which are the Czech Republic, Hungary, Latvia, Poland, and Slovenia, have never been done in any research. Even though most of the research about the impact of poverty in the agricultural sector and foreign direct investment has been done in developing countries, the research related to these countries still can’t be found. The data used by the researchers is within the period of time of 10 years, from 2005 to 2014, of annual time series data. Therefore, reviewing this chapter, it gets confirmed that the research gap prevails in this particular area, that is, no research is conducted for evaluation of poverty’s impact on FDI inflows in agriculture. Thus, in the light of suggestions of theories and empirical literature, this chapter paves the ground for building up a conceptual framework that is to describe the directions in recognizing how poverty can enhance FDI inflows in agriculture and stimulate economic growth and agricultural growth.